Exploring the experiences of teachers undertaking Educational Design Research (EDR) as a form of teacher professional learning. Issue 1 (1st January 2019) - Dunn, Ryan; Hattie, John; Bowles, Terry
ABSTRACT: The study discussed in this article examines the experiences of teachers participating in a district-wide Educational Design Research (EDR) initiative, with a particular focus on any perceived changes in teacher practices. McKenney and Reeves (2013) claimed that one of the two main goals of EDR is to benefit practice, but to date this claim has been underexplored in the literature. To test this claim, data for this quantitative study was collected from 344 teachers in an urban school district in California. The findings illustrate that EDR did enable the majority of teachers to enhance their teaching practices.